Changes in the Disclosure Obligations of the Notes to the Balance Sheet and Income Statement between 2000 and 2018 - Kerezsi, Dóra (International Journal of Engineering and Management Sciences, 2018)
The aim of the study is to present by different types of companies the information content of the supplementary annex. We can say about the economic organizations, that they must to constitute real image in financial statements about the situation of –assets, -finance and income. To appreciate the businesses is necessary the information system, which is integrated company to company. The data of financial statement prepared by accounting act are historical, concern the past. The conduct of numerous economic operators is influenced by the globalization accelerated nowadays. In this connection, it can be certainly said that the globalization affects the accounting regulation as well. In our country, the business entities falling within the scope of the aforementioned regulation are subject to Act C of 2000 on Accounting, according to which the prepared reports shall provide the external and internal stakeholders with information ensuring a true and fair overall picture of the business entities’ property, financial and profitability situation as well as future plans. In my treatise, I will highlight a part of the report i.e. the Notes providing text information in addition to the numerical data. Within this, I will present those mandatory disclosure obligations related to the balance sheet and income statement which are indispensable tools of informing the external and internal operators adequately.